1992
DOI: 10.1111/j.1399-6576.1992.tb03514.x
|View full text |Cite
|
Sign up to set email alerts
|

Continuous coeliac plexus blockade plus intermittent wound infiltration with bupivacaine following upper abdominal surgery: a double‐blind randomised study

Abstract: In this double-blind trial, we observed the effect of intermittent wound infiltration with local anaesthetic plus continuous coeliac plexus blockade on postoperative pain relief, pulmonary function, the neuroendocrine and acute phase protein response following upper abdominal surgery. In Group A (n = 10) patients received bupivacaine intermittently into the wound and continuously into the coeliac plexus following an initial bolus. A total of 862.5 mg of bupivacaine was used over 12 h with no observed toxicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
(2 reference statements)
1
5
1
Order By: Relevance
“…CWI with ropivacaine may also act through systemic reabsorption by local vascularization . Even if it remains speculative, we assume that there may be a link between the reduction of postoperative morphine consumption and the plexus coeliac blockade with local anesthetics as previously reported . A blockade of coeliac plexus in hepatic procedure led to a reduction of morphine consumption.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…CWI with ropivacaine may also act through systemic reabsorption by local vascularization . Even if it remains speculative, we assume that there may be a link between the reduction of postoperative morphine consumption and the plexus coeliac blockade with local anesthetics as previously reported . A blockade of coeliac plexus in hepatic procedure led to a reduction of morphine consumption.…”
Section: Discussionsupporting
confidence: 52%
“…A blockade of coeliac plexus in hepatic procedure led to a reduction of morphine consumption. Surgery with local infiltration allows to reduce morphine consumption and lower pain scores are reported after surgery . More recent studies also reported the reduction of morphine consumption in patients with liver metastasis and less pain experienced in hepatic arterial embolization, thermoablation of liver metastases, and hepatic refractory pain …”
Section: Discussionmentioning
confidence: 97%
“…Hamid et al. [29] demonstrated that pain relief and pulmonary function were poor even with combined wound and coeliac plexus catheters, presumably because total afferent neural blockade cannot be achieved. Intermittent bupivacaine into the rectus sheath after midline laparotomy does not decrease opioid requirement, postoperative pain or peak expiratory flow rate [30].…”
Section: Surgical Applicationsmentioning
confidence: 99%
“…head, thoracic, or abdominal trauma patients and those unable to tolerate systemic analgesics (Brennan 1993). These uses have been modified to include indwelling catheter delivery of local anesthetic nerve blocks via constant rate infusions, intermittent ‘top‐up’, or patient‐controlled mechanisms (Hamid et al. 1992; Mackenzie & Pullinger 1997; Klein et al.…”
Section: Discussionmentioning
confidence: 99%